ANALISIS PENERAPAN PP 23 DAN UU PPH PASAL 17 PADA PT. X - Lamberty, Purnamawati Helen Widjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This study aims to examine the decision of PT. X using tax rates of 2018 Government Regulation Number 23 and the applied of the rates of Article 17 Paragraph 2A of Income Tax Law will have an impact to the net income. This research using observation and interview to get the reports of company’s financial statement in 2019 and other informations those required from company. This research was conducted by visiting PT. X where is located on Taman Kota Blok B2 No. 26 Kembangan Utara, Jakarta Barat, Indonesia. The result of this study indicate the applied of the rates of Article 17 Paragraph 2A of Income Tax Law to the company would increase the company tax expenses and decrease its net profit.